2019
DOI: 10.1016/j.dib.2019.104087
|View full text |Cite
|
Sign up to set email alerts
|

The components data of fuzheng huayu extracts, cordyceps sinensis mycelia polysaccharide, gypenosides and amygdalin

Abstract: Fuzheng Huayu (FZHY) capsule is a traditional Chinese medicine composed of six Chinese medicinal herbs Tian et al. [1] and approved by China food and drug administration for liver fibrosis treatment [2] , [3] Liu et al., 2009 and Liu et al., 2005. CGA formula consisting of Cordyeps sinensis polysaccharide (CS-PS), gypenosides (G), and amygdalin (A), are derived from FZHY formula. It is necessary to identify the chemical profile of FZHY and CGA formula to describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Fuzheng Huayu (FZHY, traditional Chinese medicine) is a blend of six herbs [ 85 ]. The formulation has been approved for the treatment of liver fibrosis by the China Food and Drug Administration [ 86 ].…”
Section: Clinical Trials Of Therapies For Post-covid Lung Fibrosismentioning
confidence: 99%
“…Fuzheng Huayu (FZHY, traditional Chinese medicine) is a blend of six herbs [ 85 ]. The formulation has been approved for the treatment of liver fibrosis by the China Food and Drug Administration [ 86 ].…”
Section: Clinical Trials Of Therapies For Post-covid Lung Fibrosismentioning
confidence: 99%
“…Schisandra chinensis is one of the crucial components in the Chinese prescription, Fuzheng Huayu Recipe, to treat liver diseases mainly hepatitis B induced fibrosis (Liu et al, 2019a). Deoxyschizandrin was identified as a compound possessing the function to change the cytochrome P450 enzyme activity during hepatic fibrogenesis (Liu et al, 2019b). It was reported that the metabolism of deoxyschizandrin involved the P450 isoforms CYP3A4 and CYP3A5 (Yang et al, 2015).…”
Section: Other Compounds From Herbs or Plantsmentioning
confidence: 99%